2015
DOI: 10.1007/s00247-015-3426-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo radiologic placement of button gastrostomy: a feasibility study in children with cancer

Abstract: The procedure and devices were well tolerated and mostly effective in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…A small feasibility study of radiologically placed primary button GT in 11 children and young adults with cancer (3-20 years old) showed no major complications or short-to medium-term infections and minor complications in only two patients. 48 However, another study showed much higher rates of local infection with button GT use compared with initial GT, highlighting the need for further research. 40 The incidence of persistent gastrocutaneous fistula after GT removal has been reported as high as 45% in general pediatric populations, with duration since initial insertion the only reported significant predictive factor.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small feasibility study of radiologically placed primary button GT in 11 children and young adults with cancer (3-20 years old) showed no major complications or short-to medium-term infections and minor complications in only two patients. 48 However, another study showed much higher rates of local infection with button GT use compared with initial GT, highlighting the need for further research. 40 The incidence of persistent gastrocutaneous fistula after GT removal has been reported as high as 45% in general pediatric populations, with duration since initial insertion the only reported significant predictive factor.…”
Section: Complicationsmentioning
confidence: 99%
“…Button GT are not commonly used at initial insertion, and there is limited evidence on their use in children with cancer. A small feasibility study of radiologically placed primary button GT in 11 children and young adults with cancer (3–20 years old) showed no major complications or short‐ to medium‐term infections and minor complications in only two patients . However, another study showed much higher rates of local infection with button GT use compared with initial GT, highlighting the need for further research …”
Section: Complicationsmentioning
confidence: 99%
“…One study was translated from French 36 ; others were in English. All but two studies 17,36 were single-center, with 50% (8 of 16) undertaken in Europe, 17,22,26,[36][37][38][39][40] 44% (7 of 16) in North America, 24,25,27,[41][42][43][44] and one in Australia. 45 Study inclusion periods ranged from 3.5 to 16 years, 25,26 with average ages from 2 to 13 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…45 Study inclusion periods ranged from 3.5 to 16 years, 25,26 with average ages from 2 to 13 years. 24,36,40 Two studies focused on children undergoing BMT, 22,24 three investigated mixed populations undergoing cancer treatment with and without BMT, 26,27,38 and 69% (11 of 16) included children undergoing treatment for various malignant diseases without BMT.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation